Somnolencia diurna excesiva y riesgo suicida en estudiantes de básica superior de la Unidad Educativa Fiscomisional Juan XXIII – Yantzaza - Luzuriaga Alberca, Thayli Anabel (2023)
Sleep disorders constitute critical risk factors for suicidal behaviors, because sleep disturbances, such as insomnia, nightmares and in particular, excessive daytime sleepiness, were associated with subsequent suicidal thoughts and plans, during one-year follow-up, even after adjusting for depression/anxiety and sleep-related complaints, since biologically, they share the same mechanisms, such as reduced serotonin concentrations or activities and decreased activity of the hypothalamic-pituitary-adrenal axis. The present study aimed to identify the presence of excessive daytime sleepiness, to detect suicidal risk and to know the relationship between excessive daytime sleepiness and suicidal risk in high school students of the Unidad Educativa Fiscomisional Juan XXIII - Yantzaza, period September - June 2022. It was a descriptive-correlational study, with a mixed approach, prospective cross-sectional type, conformed by 159 students, to whom the Epworth Sleepiness Scale and the Suicide Assessment Questions were applied. Of these, 18.87% (n=30) presented excessive daytime sleepiness, and 29.56% (n=47) presented suicidal risk, predominantly among 13-year-old females. On analyzing the variables and using Pearson's Chi-square statistical association test, a statistically significant relationship was obtained with a p-value of 0.022626, concluding that excessive daytime sleepiness directly influences the development of suicidal risk in high school students